Paving the way for the use of Statherin-Derived Peptide (StN15) to control caries through acquired pellicle and biofilm microbiome engineering: Proof-of-concept in vitro/in vivo studies - Araujo, Tamara Teodoro; Debortolli, Ana Luiza Bogaz; Carvalho, Thamyris Souza; Rodrigues, Chelsea Maria Vilas Boas Feitosa; Dionizio, Aline; de Souza, Beatriz Martines; Vertuan, Mariele; Ventura, Talita Mendes; Grizzo, Larissa Tercilia; Marchetto, Reinaldo [UNESP]; Henrique Silva, Flavio; Chiaratti, Marcos; et al. (Elsevier, 2025)
Objective: This proof-of-concept sequence of in vivo/in vitro studies aimed to unveil the role of acquired enamel pellicle (AEP) engineering with statherin-derived peptide (StN15) on the AEP protein profile, enamel biofilm microbiome in vivo and on enamel demineralization in vitro. Design: In vivo studies, 10 volunteers, in 2 independent experiments (2 days each), rinsed (10 mL,1 min) with: deionized water (negative control) or 1.88 × 10−5 M StN15. The AEP, formed along 2 h and the biofilm, along 3 h, were collected. AEP was analyzed by quantitative shotgun-label-free proteomics. The enamel biofilm microbiome was evaluated using 16S-rRNA Next Generation Sequencing (NGS). An in vitro model with microcosm biofilm was employed. Bovine enamel samples (n = 72) were treated with 1) Phosphate-Buffer-Solution (PBS), 2) 0.12 %Chlorhexidine, 3) 500ppmNaF; 4) 1.88 × 10−5MStN15; 5) 3.76 × 10−5MStN15 and 6) 7.52 × 10−5MStN15. Biofilm was supplemented with human saliva and McBain saliva and cultivated for 5 days. Resazurin, colony forming units (CFU) and Transversal Microradiography Analysis-(TMR) were performed. Results: Proteomic results showed several proteins with acid-resistant, calcium-binding, and antimicrobial properties in the StN15 group. The microbiome corroborated these findings, reducing bacteria that are closely related to dental caries in the StN15 group, compared to the PBS. The microcosm biofilm showed that the lowest concentration of StN15 was the most efficient in reducing bacterial activity, CFU and enamel demineralization compared to PBS. Conclusion: StN15 can effectively alter the AEP proteome to inhibit initial bacterial colonization, thereby mitigating enamel demineralization. Future research should explore clinical applications and elucidate the mechanisms underlying the protective effects of StN15.
Keywords: Acquired enamel pellicle; Biofilm, Dental caries, Demineralization; Statherin